2002
DOI: 10.1111/j.1834-7819.2002.tb00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus: Causes, diagnosis and management

Abstract: Oral lichen planus (OLP) is a chronic inflammatory disease of unknown etiology. In this paper we review the clinical and histological features of OLP, process of OLP diagnosis, causes of OLP, management of OLP patients and medical treatment of OLP lesions. Approximately 0.2 per cent OLP patients develop intra-oral carcinoma each year compared with approximately 0.005 per cent Australian adults. Possible mechanisms of increased oral cancer risk in OLP patients are presented. The aims of current OLP therapy are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
1
52

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 38 publications
2
135
1
52
Order By: Relevance
“…It has been observed that the oral lesions may persist upto 25 years [4] and precipitate during the periods of stress. [13] In the present case it is reported in a 27 year old male patient.…”
Section: Discussionmentioning
confidence: 98%
“…It has been observed that the oral lesions may persist upto 25 years [4] and precipitate during the periods of stress. [13] In the present case it is reported in a 27 year old male patient.…”
Section: Discussionmentioning
confidence: 98%
“…12 Sugerman et al observed wider atd angles. 13 Mathew et al found an increased frequency of ulnar and radial loops than the arches and whorls in cleft lip with or, without cleft palate patients compared to controls. 12 ImeneNamouchi conducted a study on Tunisian population to analyze eventual differences between men and women and between individuals according to their geographical distribution.…”
Section: Studies Based On Dermatoglyphics To Identify Various Systemimentioning
confidence: 96%
“…Sometimes, however, the causative allergen cannot be specified. (18) Sometimes the removal of the identified allergen does not result in regression of the lesions. (19) Topical corticosteroids are used to decrease inflammation and alleviate symptoms.…”
Section: Treatment Of Ollmentioning
confidence: 99%